Deterministic Factors of Thai Cassava Prices: Multi-Uses of Cassava from Food, Feed, and Fuel Affecting on Thai Cassava Price Volatility - Treesilvattanakul, Krissana (KnE Life Sciences, 2016)
Cassava (Manihot esculaenta Crantz) is one of the world important carbohydrate and calorie crops. The significance of cassava lies hidden in the uses of cassava products ranging from food to industrial sectors. In recent years, the Thai cassava price is markedly fluctuated and became a challenge for farmers, collectors, and manufacturers of cassava products to manage their production and processing. This paper examines factors considerably influencing the volatility of Thai cassava price. We further attempt in reporting the weighted importance of each factor including the pattern of their relationship with respect to cassava price. Research methodology will be conducted into two dimensions: from the perspective of only cassava price and from the combination of cassava price and its influencing factors. The result shows the seasonality nature of cassava price, while the fluctuation is caused by the several interrelated factors. Keywords: Cassava, Price, Utilization, Thailand.